Dynamic 13C MR spectroscopy as an alternative to imaging for assessing cerebral metabolism using hyperpolarized pyruvate in humans. Issue 3 (22nd October 2021) - Ma, Junjie; Pinho, Marco C.; Harrison, Crystal E.; Chen, Jun; Sun, Chenhao; Hackett, Edward P.; Liticker, Jeff; Ratnakar, James; Reed, Galen D.; Chen, Albert P.; Sherry, A. Dean; Malloy, Craig R.; et al.
Abstract : Purpose: This study is to investigate time‐resolved 13 C MR spectroscopy (MRS) as an alternative to imaging for assessing pyruvate metabolism using hyperpolarized (HP) [1‐ 13 C]pyruvate in the human brain. Methods: Time‐resolved 13 C spectra were acquired from four axial brain slices of healthy human participants (n = 4) after a bolus injection of HP [1‐ 13 C]pyruvate. 13 C MRS with low flip‐angle excitations and a multichannel 13 C/ 1 H dual‐frequency radiofrequency (RF) coil were exploited for reliable and unperturbed assessment of HP pyruvate metabolism. Slice‐wise areas under the curve (AUCs) of 13 C‐metabolites were measured and kinetic analysis was performed to estimate the production rates of lactate and HCO 3 ‐ . Linear regression analysis between brain volumes and HP signals was performed. Region‐focused pyruvate metabolism was estimated using coil‐wise 13 C reconstruction. Reproducibility of HP pyruvate exams was presented by performing two consecutive injections with a 45‐minutes interval. Results: [1‐ 13 C]Lactate relative to the total 13 C signal (tC) was 0.21–0.24 in all slices. [ 13 C] HCO 3 ‐ /tC was 0.065–0.091. Apparent conversion rate constants from pyruvate to lactate and HCO 3 ‐ were calculated as 0.014–0.018 s −1 and 0.0043–0.0056 s −1, respectively. Pyruvate/tC and lactate/tC were in moderate linear relationships with fractional gray matter volume within each slice. White matter presented poor linear regression fit with HP signals, and moderate correlations of the fractional cerebrospinal fluid volume with pyruvate/tC and lactate/tC were measured. Measured HP signals were comparable between two consecutive exams with HP [1‐ 13 C]pyruvate. Conclusions: Dynamic MRS in combination with multichannel RF coils is an affordable and reliable alternative to imaging methods in investigating cerebral metabolism using HP [1‐ 13 C]pyruvate.